Diversity of egg parasitoids attacking Dalbulus maidis (Hemiptera: Cicadellidae) populations at low and high elevation sites in Mexico and Argentina - Moya Raygoza, Gustavo (2012)
The corn leafhopper, Dalbulus maidis (DeLong & Wolcott), is one of the most important pests of maize in Latin America because of its efficiency as a vector of 3 species of plant pathogens. In spite of its significance, however, little is known about its egg parasitoids. In this study, we present new data on D. maidis egg parasitoids in Mexico and Argentina. We surveyed the egg parasitoids in 2 locations: Mexico and Argentina, representing the farthest expansion of the D. maidis populations from Mexico. Using maize plants with sentinel eggs, parasitoids were surveyed in central Mexico and northwestern Argentina, at both low (<1,000) and high (>1,000) elevation sites, during 2 maize-growing wet seasons. Parasitoids of the families Mymaridae and Trichogrammatidae were found in both countries. Argentinean sites showed the highest richness, with 10 species, whereas in Mexico we found 6 species. Also, the Shannon diversity index was 1.6 times greater in Argentina than in Mexico. Higher percentages of parasitized eggs were recorded at the low elevation sites in both Mexico and Argentina. Anagrus breviphragma Soyka, a generalist parasitoid, was the only species found attacking eggs of D. maidis in both Mexico and Argentina at both high and low elevations.